Modelling Lichen Abundance for Woodland Caribou in a Fire-Driven Boreal Landscape - Joseph Silva; Scott Nielsen; Clayton Lamb; Christine Hague; Stan Boutin (Forests, 2019)
Woodland caribou (Rangifer tarandus caribou) are reliant on Cladonia spp. ground lichens as a major component of their diet and lichen abundance could be an important indicator of habitat quality, particularly in winter. The boreal forest is typified by large, stand-replacing forest fires that consume ground lichens, which take decades to recover. The large spatial extent of caribou ranges and the mosaic of lichen availability created by fires make it challenging to track the abundance of ground lichens. Researchers have developed various techniques to map lichens across northern boreal and tundra landscapes, but it remains unclear which techniques are best suited for use in the continuous boreal forest, where many of the conflicts amongst caribou and human activities are most acute. In this study, we propose a two-stage regression modelling approach to map the abundance (biomass, kg/ha) of Cladonia spp. ground lichens in the boreal forest. Our study was conducted in Woodland Caribou Provincial Park, a wilderness-class protected area in northwestern Ontario, Canada. We used field sampling to characterize lichen abundance in 109 upland forest stands across the local time-since-fire continuum (2–119 years-since-fire). We then used generalized linear models to relate lichen presence and lichen abundance to forest structure, topographic and remote sensing attributes. Model selection indicated ground lichens were best predicted by ecosite, time-since-fire, and canopy closure. Lichen abundance was very low (<1000 kg/ha) across the time-since-fire continuum in upland forest stands with dense tree cover. Conversely, lichen abundance increased steadily across the time-since-fire continuum in upland forest stands with sparse tree cover, exceeding 3000 kg/ha in mature stands. We interpolated the best lichen presence and lichen abundance models to create spatial layers and combined them to generate a map that provides a reasonable estimation of lichen biomass (R2 = 0.39) for our study area. We encourage researchers and ...